(MISTY) PLACES IN THE POETRY OF PAUL CELAN. PNEUMATIC JEWISHNESS AND PNEUMATIC GEOPOETICS - Roszak, Joanna (Porównania, 2012)
The fact of taking up themes of not being settled, of escapes and of painful returns into the places of trauma, connotes issues of the witness and rhetoric of the memory obsession, its „revenge”. The article is aimed at analyzing Paul Celans poetry through a geopoetic prism that allows me to construct an interpretation around the indicated place: Gewiddert, in which Drohobych is mentioned. Therefore, Celan gives one an obvious excuse for geopoetic research. In addition, as it appears to me, a type of lyric poetry, especially firmly related to “geo” in Celan’s case, is an elegy; one might even venture to create a sub-genre: elegies of place – a famous poem by Antoni Słonimski would be among them. My reflection on 'the Jewish fate', articulated by a Jewish voice, will concentrate on biographical signals (chronotopic) encrypted in a poem (geopoetry), also understood from a geopoetic perspective – connected with the (new) biographism (hermeneutics of the place and the situation), indicating various concepts of places.